2013
DOI: 10.1177/003172171309400508
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Choices of Sex Education

Abstract: Giving a quiz or a test after sex education courses may not be the best way to ensure that students use what they've learned in class to make good decisions after class. Possessing facts about sex does not guarantee that students will adopt healthy strategies and make wise decisions in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…In addition, prior research has revealed that perceived extrinsic goal structures are related to maladaptive patterns of beliefs and attitudes (e.g., Anderman et al, 2011;Anderman & Won, 2019). The null relations of perceived extrinsic goal structures with adaptive motivational beliefs reported in the present study, as well as the relations with maladaptive beliefs and attitudes reported in previous research, suggest that an extrinsic goal structure does not benefit students' motivation or learning outcomes in health classrooms (Hamilton, Sanders, & Anderman, 2013).…”
Section: Classroom Goal Structures and Students' Motivation In Health...contrasting
confidence: 64%
“…In addition, prior research has revealed that perceived extrinsic goal structures are related to maladaptive patterns of beliefs and attitudes (e.g., Anderman et al, 2011;Anderman & Won, 2019). The null relations of perceived extrinsic goal structures with adaptive motivational beliefs reported in the present study, as well as the relations with maladaptive beliefs and attitudes reported in previous research, suggest that an extrinsic goal structure does not benefit students' motivation or learning outcomes in health classrooms (Hamilton, Sanders, & Anderman, 2013).…”
Section: Classroom Goal Structures and Students' Motivation In Health...contrasting
confidence: 64%
“…Nevertheless, challenges to this work are inevitably evident, with professional burnout, difficulties working with families, boundary setting, funding and emotional strains being prominent (Bradley, 2018). With this, the need for organisational support to maintain mentors’ wellbeing and increase the effectiveness of mentoring is well documented (Freedman, 1992; Grossman and Furano, 1999; Hamilton and Hamilton, 1992; DuBois et al , 2002). While offering valuable insights, limitations on generalisability restrict the current evidence.…”
Section: Introductionmentioning
confidence: 99%